School-induced fatigue: Theoretical analysis of the concept of school burnout - Kleszczewska-Albińska, Angelika (Journal of Psychological Perspective, 2024)
School burnout is a set of detrimental symptoms that include emotional exhaustion, cynicism, and reduced personal accomplishment. In children and adolescents it is associated with many physical and mental health problems, including heart diseases, hormonal disorders, disrupted sleep quality, depressive symptoms, and diminished life satisfaction. It corresponds with a higher likelihood of poor academic performance and drop-out rates. The text includes a theoretical analysis of factors corresponding with the development and maintenance of school burnout. The data presented in the literature proves that students dealing with extreme schoolwork overload, accompanied with poor time management, and unrealistic goals, faced with excessive family demands, experiencing disturbances in sleep habits, poor eating habits, and limited or no physical exercise are more prone to develop and sustain symptoms of school burnout. Besides the excessive workload and problems in relationships with parents and peers among risk factors there are usually mentioned feelings of lack of control over things, high demands, and pressure an individual experiences. Protective factors include social support and a positive school atmosphere. Application of knowledge concerning school burnout in real educational settings may result in increase of well-being and resilience of students, and decrease in symptoms of mental problems. It will also help create a meaningful school environment.